Identificación y evaluación de riesgos ante una posible erupción volcánica en la empresa Licorec S.A ubicada en el sector Lasso en el período 2016 - Muñoz Noroña, Esteban Fabricio (2016)
The following research has been done in order to prevent risks to the impacts which can cause a possible volcanic eruption into the “Licorec S.A” enterprise, which is located in Lasso neighborhood, Tanicuchi parish , Latacunga Canton, which is to few kilometers of the Colossus, whereby preventive measures of security were taken in order to protect the workers’ physical integrity, through the design and implementation of an emergency plan in order to face a natural disaster of great magnitude. This document will represent an obligatory use for the staff and visitors who can be into the installations in case of an unwanted event.